Blockchain-Based Data Bank for Music Royalty Protection in Indonesia - Marseda, Achmad Trisana; Rosidah, Erni; Lany, Arman (Research Horizon, 2025)
The use of songs on digital platforms without permission and royalty payments has caused economic losses of up to 1.2 trillion IDR per year for creators, due to weak manual tracking systems and database fragmentation. This study aims to formulate an integrated data bank model based on blockchain, Application Programming Interface, and audio fingerprinting to improve the transparency of royalty distribution in accordance with the Copyright Law and Government Regulation Number 56/2021, as well as fulfilling trade aspects related to intellectual property rights article 14. through a normative juridical approach, this study analyzes the legal gaps between national regulations and global practices and examines the implementation of real-time tracking technology. The results are expected to produce technical policy recommendations for system harmonization, increasing royalty distribution accuracy to 85%, and strengthening law enforcement through digital evidence. This research supports the National Medium-Term Development Plan 2024-2025 target of increasing the contribution of the creative economy by 7% and strengthening Indonesia's position in the global Intellectual Property Rights regime through adaptive and sustainable technology-based solutions.